Synthesis, Antioxidant, and Preliminary Antitumor Activities of New Curcumin Analogues - Yasser Fakri Mustafa (Journal of Global Pharma Technology, 2020)
Curcumin is a molecule gifted from nature to improve human health by its multiple biological activities. However, the application of curcumin in therapeutics is limited mainly due to its poor aqueous solubility, insignificant chemical stability, and low cellular uptake. To address some of these drawbacks, eight analogues of curcumin were synthesized starting from simple molecules. Characterization of the chemical structures of these analogues was documented by interpretation of their IR, 1H-NMR, and 13C-NMR spectra. Biological activities of the synthesized analogues were studied by comparing their activities with those of curcumin. This biological assessment included examining the antioxidant capacity via DPPH and hydroxyl radical scavenging activity tests, and screening the preliminary antitumor activity against MCF-7 and HeLa cancer cell lines by MTT test. Depending on the resulted data, it was found that these analogues have the comparable biological activities but with better stability and water solubility in comparison with curcumin. It is postulated that such analogues may be useful clues to improve the therapeutic applications of curcumin.Keywords: Curcumin, Synthesis, Analogues, Antioxidant, Antitumor.